When Does Identifying With Christ’s Suffering Help? A Moderated Moderation Analysis - Lee, Sammi (Journal of psychology and theology, 2025)
While religious coping has been extensively linked with positive outcomes, many emic religious coping resources have been insufficiently explored from a psychological perspective. This study investigated the efficacy of a Christian meaning-making coping method, identification with Christ’s suffering, in ameliorating the negative relation between stressor severity and well-being (i.e., anxiety, depression, life satisfaction) in an international sample of 376 practicing Christians who experienced a distressing event in the past 6 months. In addition, we investigated how attachment to God further moderates the efficacy of the moderating effect of identification with Christ. Results indicated at lower levels of stressor severity and anxious attachment to God (corresponding to more secure attachment to God), identifying with Christ resulted in reduced anxiety. In contrast, at higher levels of stressor severity and anxious attachment, identifying with Christ resulted in reduced depressive symptoms. Identifying with Christ had a significant main effect with satisfaction with life that was not moderated by either severity of stressor or attachment to God. No significant findings were observed for avoidant attachment.